2021
DOI: 10.1186/s12877-021-02391-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biological age and all-cause mortality by 12-lead electrocardiogram in patients without structural heart disease

Abstract: Background There is a well-established relationship between 12-lead electrocardiogram (ECG) and age and mortality. Furthermore, there is increasing evidence that ECG can be used to predict biological age. However, the utility of biological age from ECG for predicting mortality remains unclear. Methods This was a single-center cohort study from a cardiology specialized hospital. A total of 19,170 patients registered in this study from February 2010 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…In this study, we have achieved comparable accuracy to previous studies in age predictions (23)(24)(25)(26). The ECG-age is correlated with mortality which was known by many heuristic studies (24)(25)(26). Here, we demonstrated that ECG-age was not only correlated with mortality but also extensive CVD-related outcomes.…”
Section: Data Availability Statementsupporting
confidence: 80%
See 3 more Smart Citations
“…In this study, we have achieved comparable accuracy to previous studies in age predictions (23)(24)(25)(26). The ECG-age is correlated with mortality which was known by many heuristic studies (24)(25)(26). Here, we demonstrated that ECG-age was not only correlated with mortality but also extensive CVD-related outcomes.…”
Section: Data Availability Statementsupporting
confidence: 80%
“…In this study, we have achieved comparable accuracy to previous studies in age predictions (23)(24)(25)(26). The ECG-age is correlated with mortality which was known by many heuristic studies (24)(25)(26).…”
Section: Data Availability Statementsupporting
confidence: 77%
See 2 more Smart Citations
“…a “Heart Age Gap”. A Heart Age can either be determined by translating risk factor scores to what age a resultant score would represent in an individual with no risk factors, or it can be based on electrocardiographic changes 7 14 . Describing the risk to the patient using Heart Age has been reported to reduce metabolic risk factors and may have the advantage of being easily understood by the patient 11 , 15 .…”
Section: Introductionmentioning
confidence: 99%